2013
DOI: 10.1016/j.archger.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicidal ideation, attempts, and completed suicide rate in Chinese aging populations: A systematic review

Abstract: Background As one of the leading causes of death around the world, suicide is a global public health threat. Due to the paucity of systematic studies, there exist vast variations in suicide ideation, attempts and suicide rates between various regions of Chinese aging communities. Objectives Our systematic study aims to 1) identify studies describing the epidemiology of suicidal ideation, suicide attempts and behaviors among global Chinese communities; 2) conduct systematic review of suicide prevalence; 3) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 26 publications
1
27
2
1
Order By: Relevance
“…Compared with previous studies, the prevalence in this study (19.5%) was much higher than that among community‐dwelling elders in rural and urban China (2.2–16.7%; Simon et al . ). Because suicidal thoughts are a predictor for suicide, this finding indicated that Chinese rural institutional elders were at high risk of suicide.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared with previous studies, the prevalence in this study (19.5%) was much higher than that among community‐dwelling elders in rural and urban China (2.2–16.7%; Simon et al . ). Because suicidal thoughts are a predictor for suicide, this finding indicated that Chinese rural institutional elders were at high risk of suicide.…”
Section: Discussionmentioning
confidence: 97%
“…; Simon et al . ). In China, the burden of elderly suicide is particularly significant in rural areas in which suicide rate is fivefold higher than that of urban regions (Chiu et al .…”
Section: Introductionmentioning
confidence: 97%
“…Of course, we could use “prevalence” to refer to “suicide ideation” [5], due to the fact that ideation could be studied in cross-sectional studies and could be maintained through long periods of time in some people. Although suicide ideation is not always present all the time, except in some severe episodes of major depression, I think that we can use the terms point prevalence, period prevalence or lifetime prevalence for suicide ideation, as some authors have done it [5], in order to identify people with any suicide ideation at one specific point, at a specified period or at any time in their life, respectively.…”
mentioning
confidence: 99%
“…Although suicide ideation is not always present all the time, except in some severe episodes of major depression, I think that we can use the terms point prevalence, period prevalence or lifetime prevalence for suicide ideation, as some authors have done it [5], in order to identify people with any suicide ideation at one specific point, at a specified period or at any time in their life, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation